Time-scheduled exposure method for full-color high diffraction efficiency and uniformity of a photopolymer. (December 2022) - Wu, Hui-Ying; Shin, Chang-Won; Kwon, Ki-Chul; Lee, Kwon-Yeon; Kim, Nam
Highlights: Time-scheduled exposure method for full-color reflection recording is proposed. The reactivity of the photopolymer to exposures is different at the three wavelengths. The pre-exposure times of each laser are adjusted to make the diffraction efficiencies more uniform. The full-color grating with high diffraction efficiency is verified experimentally. Abstract: A full-color reflection holographic optical element (HOE) with uniform diffraction efficiency, achieved via time-scheduled exposure, is proposed in which 660, 532, and 473 nm wavelengths are used for recording. To enhance the diffraction efficiency, the exposure energy of three wavelengths should be controlled to react uniformly in the photopolymer. The photopolymer's optical characteristics present that the absorptance of the three wavelengths differs, moreover, the reactivity of the photopolymer to exposures is variant at the three wavelengths. The high-efficiency full-color HOE is implemented by determining the pre-exposure times of the three lasers for a set beam intensity. In order to verify the proposed method, we conduct repetitive optical experiments and analyze the results. Finally, a full-color reflection hologram is manufactured with an average efficiency of 61.6 % (standard deviation, 0.5) when the beam intensity of the three lasers is 0.4 mW/cm 2 . The reconstructed images of the full-color hologram show good uniformity and color reproduction.